النشاط الثوري لفيديرالية جبهة التحرير الوطني بفرنسا ودوره في كسب أصدقاء للثورة الجزائرية (El-Wahat Journal for Research and Studies, 2025)
The Residence Of Algerian Immigrants In France And Their Mixing With Unions, Labor Organizations And Left -Wing Parties Led To The Crystallization Of National Awareness And The Assignment Of Political Action, Which Revealed To The French And International Public Opinion Justice And The Legitimacy Of The Algerian Struggle In Light Of The Colonial Hegemony, And After The Success Of The National Liberation Front In France Through The Guerrilla Operations And The Wide Activity Of Its Activistsin All French Provinces.A Lot Of Historical Data Has Changed, So Anti-French Repression Campaigns Have Begun And The Logistical Support Of The National Liberation Revolution Has Multiplied Throughout The World. National And Foreign Historical Writings, Particularly After 1957, And Specifically Following The Honorable Work Of Support Networks And Suitcase Campaigns, As A Result, The World Has Discovered The Reality Of Algerians' Terrible Arbitrary Colonial Repression, Accordingly, The Honorable Positions Of Many French And International Figures Have Emerged.Keywords : International Support, Guerrilla Operations, Torture, Revolution, Federalism Of France.